The infrastructure needs of a growing organisation: a study conducted in an IT company - Arendse, Teresia (Department of Mechanical Engineering, 2014)
The aim of this research is to focus on the growth demands of a specific organisation. It explores the need of a growing organisation to have an operational support structure that supports its growth.